2009
DOI: 10.1143/jjap.48.04c162
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-Selectivity of Organic Photoconductive Devices by Solution Process

Abstract: Organic photoconductive devices sensitive to blue, green, and red lights were achieved using poly(9,9-dioctylfluorenyl-2,7-diyl)-co-1,4benzo-(2,1,3)-thiadiazole (F8BT), rhodamine 6G-doped poly(9,9-dioctylfluorene) (PFO), nickel tetrakis(tert-butyl)phthalocyanine-doped PFO, respectively. These organic materials can be coated by a solution process, which leads us to realize the low fabrication cost and the large device area. Selectivity of spectral responses of these organic films were good enough to divide the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…Fukuda et al [ 147 ] have developed a three-color sensor based on different organic materials with pixels that separately absorb blue, green and red light (see Figure 9 a(i)). The organic materials were initially selected by a simple screening of the literature and relatively simple OPDs (ITO/organic layer/Al) comprised of neat solution-processed fi lms were prepared.…”
Section: Blue-sensitive Opdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fukuda et al [ 147 ] have developed a three-color sensor based on different organic materials with pixels that separately absorb blue, green and red light (see Figure 9 a(i)). The organic materials were initially selected by a simple screening of the literature and relatively simple OPDs (ITO/organic layer/Al) comprised of neat solution-processed fi lms were prepared.…”
Section: Blue-sensitive Opdsmentioning
confidence: 99%
“…The FWHM of the blue OPD was ≈120 nm (photocurrent) although the EQE was only 0.12% at -2.3 V due to it being a homojunction. [ 147 ] Indeed, homojunctions generally tend to give low EQEs. [ 216 ] When F8BT ( N1 ) was blended with various electronaccepting materials, the blue-sensitive OPD performance was improved.…”
Section: Blue-sensitive Opdsmentioning
confidence: 99%
“…At present, indium tin oxide (ITO) is widely used for the main transparent electrode films in liquid crystal display panels and solar batteries made of organic electroluminescent materials, touch panels, flat panel displays, and so on [1][2][3][4][5][6]. However, indium, which is a rare metal, is expensive, and its supply is limited.…”
Section: Introductionmentioning
confidence: 99%
“…A previous paper demonstrated superior color selectivity of solution-processed organic photoconductive devices at blue, green, and red regions [6]. A low carrier recombination probability in an organic layer is important factor for the efficient photo-excited carrier transport to electrodes.…”
mentioning
confidence: 98%
“…By now, several research groups reported novel organic devices fabricated by solution processes, such as photovoltaic cells [1,2] and sensors [3]. In addition, color selective organic photoconductive devices have been attracting considerable attention for stacked organic image sensor instead of Sibased charge coupled devices and complementary metal oxide semiconductor sensors [4][5][6]. This is because absorption coefficients of several organic materials are higher than that of Si at a visible wavelength region.…”
mentioning
confidence: 99%